Improve app interface design for taxi in Malaysia: case study meter on app / Mohamad Zuhairi Mohamad Zaimanrus - Mohamad Zaimanrus, Mohamad Zuhairi (2019)
The purpose of this research is to study the interface design for metered taxi mobile application. This study will be comprehensive about good and bad in making interface design included the colour, layout, purpose, importance and method in creating interface design for metered taxi mobile application. Today, there were a lot of mobile applications that have been created to fulfil the need of mobile users. This is because mobile app makes it easy for many users in doing their daily work including transportation such as metered taxi. Creating an interface design must focusing on the quality of its user experience (UX). A good user experience (UX) is the difference between successful apps and unsuccessful ones. This is because mobile users seek for an ease of use, fast connection or loading time and delight during interaction. Therefore, interface design plays a big role in mobile app. If the app wants to succeed, the designer must consider user experience (UX) to be a major aspect of design. However, different things for metered taxi is because it is hardly to find and at the same time the tracking mobile app for metered taxi is not well-known by many mobile users. One of metered taxi tracking app that already been launched is ‘Meter on’ by SPAD. But this app seems to be a failure. The reason is because interface design for the metered taxi mobile app itself does not attracting and reliable for the users. So, as a designer, creating the best interface design for mobile app is really important so that users will attracted to use the mobile app. The researcher goals for this thesis is to study more about the best interface design for metered taxi mobile app so that at the same time metered taxi will be known wide.